When husband migrate: effects of international migration of husbands on fetal outcomes, body mass index and gestational weight of female spouses that stay behind - Renuka Jayatissa; Kolitha Wickramage; Buddhini Herath Denuwara; Himali Herath; Ranbanda Jayawardana; Amila Gayan Perera; Nawamali De Alwis (BMC, 2022)
Abstract Background International labour migration continues to be an integral component in Sri Lanka's economic development. Previous research indicates an adverse perinatal outcome in association with low maternal pre-pregnancy body mass index (PBMI) and gestational weight gain (GWG). However, evidence of this association is limited in migrant families. This study aims to investigate the associations between PBMI, GWG among lactating mothers (LM), and fetal outcomes in migrant households, where the father is the migrant worker. Methods A secondary data analysis was done using a nationally representative sample of 7,199 LM. There were 284 LM whose husbands were international migrant workers. Maternal factors were taken as PBMI<18.5 kg/m2 and GWG<7kg. Preterm birth and low birth weight (LBW) were taken as fetal outcomes. Binary logistic regression was performed to assess the associated factors. Results There was significant difference between LM from migrant and non-migrant households with regards to place of residency, ethnicity, household monthly income, household food security, average household members, husband's education and husband's age. Among migrant, PBMI<18.5 kg/m2 was associated with current BMI and mode of delivery. Migrant LM had significantly higher weight gain (≥12 kg) during pregnancy (p=0.005), were multiparous (p=0.008), delivered in private hospital (p=0.000), lesser percentage of underweight (p=0.002) and higher birthweight (p=0.03) than non-migrant LM. Logistic regression model revealed that for each kilogram increment in birthweight and GWG, preterm delivery decreased by 89%(OR=0.11;95%CI:0.04-0.28) and LBW decreased by 12%(OR=0.89;95%CI:0.81-0.97) respectively. Caesarean deliveries were positively associated with low GWG. Conclusion Our study showed LM in migrant families had invested remittances to utilize private health facilities for deliveries, to improve weight gain during pregnancy and adequate PBMI to deliver higher birth weight babies. In depth study is needed to understand further utilisation of remittances to improve fetal outcomes by increasing birthweight and GWG in migrant families.